(untitled) (Scientific journal of the Fergana State University, 2024)
Coccinellids (Coleoptera, Coccinellidae) are representatives of hardy species of practical importance. They benefit by feeding on pests such as aphids, mites, coccids, thrips, and spider mites. Within the Coccinellidae family, there are also species that damage cultivated plants. Like the imago, the larvae of the ants have a predatory lifestyle, and they are also used as entomophages in biological control. The article presents new information on the trophic relationship and food spectrum of coccinellids